2021
DOI: 10.1111/avsc.12606
|View full text |Cite
|
Sign up to set email alerts
|

Successful transfer of species‐rich grassland by means of green hay or threshing material: Does the method matter in the long term?

Abstract: Questions:We investigated the transfer of seeds from species-rich grassland using green hay and seed material from on-site threshing to answer the following questions: do these two methods differ in terms of restoration success; and how do the two methods behave in their long-term effect concerning species composition and species presence? Location: Styria, Austria. Methods:We harvested seed material of a species-rich Arrhenatherion meadow by green hay and on-site threshing and transferred it to a receptor sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…Seed availability can vary significantly at the national and regional levels [61,71,75]. Alternative, well-developed techniques, such as revegetation by hay transfer or on-site threshing [34,96], are often not feasible on the required scales and are only viable options for smaller solar farms or sub-areas. The agricultural production of seeds from regional provenances currently appears to be the only option for providing high-quality material for large-scale ecological restoration [78], as required for biodiversity-enhancing solar parks.…”
Section: Criteria For the Composition Of Pollinator-friendly Site-ada...mentioning
confidence: 99%
“…Seed availability can vary significantly at the national and regional levels [61,71,75]. Alternative, well-developed techniques, such as revegetation by hay transfer or on-site threshing [34,96], are often not feasible on the required scales and are only viable options for smaller solar farms or sub-areas. The agricultural production of seeds from regional provenances currently appears to be the only option for providing high-quality material for large-scale ecological restoration [78], as required for biodiversity-enhancing solar parks.…”
Section: Criteria For the Composition Of Pollinator-friendly Site-ada...mentioning
confidence: 99%
“…Spreading hay with diaspores is applied [16], often in combination with the removal of the top layer of soil [17,18]. Green hay spreading is used less frequently-it is possible only at small distances from donor stands [19,20]. Another method involves the production of seedlings, which is recommended especially when introducing rare and endangered species [21].…”
Section: Introductionmentioning
confidence: 99%
“…Research on various methods of restoring meadow ecosystems showed that the most effective method was green hay transfer, resulting in the restored community being the most similar to the donor meadow [27]. Schaumberger et al [20] emphasise that the choice of restoration method ultimately depends on cost and various circumstances, it is important that a large proportion of the transferred species can become established.…”
Section: Introductionmentioning
confidence: 99%